2014
DOI: 10.5388/aon.2014.14.3.191
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Standardized Telephone Counseling Guidelines on Symptom Management for Patients Discharged after Colorectal Cancer Surgery

Abstract: 연구의 필요성세계적으로Purpose: This study was carried out to develop standardized telephone counseling guidelines regarding symptom management for patients discharged after colorectal cancer surgery, and to apply and assess it in practice in order to increase patient satisfaction and compliance level. Methods: Five frequent symptoms; pain, diarrhea, constipation, bowel obstruction and wounds were extracted by a preliminary survey. Results: For wound and bowel obstruction, the most frequent applied guideline was ER recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…However, to verify the difference between the relevant variables, future research should include multidimensional variables related to individual characteristics, disease-related characteristics, environmental characteristics of medical institutions and general characteristics of nurses and patients. 34…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to verify the difference between the relevant variables, future research should include multidimensional variables related to individual characteristics, disease-related characteristics, environmental characteristics of medical institutions and general characteristics of nurses and patients. 34…”
Section: Resultsmentioning
confidence: 99%
“…The nurses’ and patients’ recognition of the importance of discharge plans was slightly lower, and in the case of the patients, performance was unusually higher than importance. 33,34 This finding might have resulted from a reduction in patient satisfaction because the discharge education currently conducted at the clinical site is implemented based on the educational needs identified by nurses in accordance with formal procedures, as opposed to their proper identification in collaboration with patients. Therefore, nurses should provide truthful information that can satisfy patients by evaluating their individualised educational needs before discharge and providing specific information about plans after discharge.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study were consistent with previous studies [ 12 , 27 ], which reported that the more symptoms experienced, the lower the quality of life. The subjects of this study mainly showed high symptoms such as fatigue, pain, constipation, diarrhea, and distress, which are common symptoms after colorectal cancer surgery [ 42 ]. The symptom experience was similar.…”
Section: Discussionmentioning
confidence: 99%